Research results of the screw dispenser of dry bulk feed components - S. Yu. Bulatov; A. N. Pronin (Аграрная наука Евро-Северо-Востока, 2024)
In the production of compound feeds, it is necessary to follow the recipe at the time of introducing all the necessary components, for which various types of dispensers are used. Currently, automatic dosing systems are widely used, providing increased dosing accuracy. However, individual settings of such systems are required for each component, which makes the work of operators harder. The article describes the design of a technical device containing a main and an additional screw and allowing components with different physical and mechanical properties to be weighed at the same tuning parameters. A brief description of the dispenser's workflow is given, the research factors and criteria for evaluating its work are listed. The influence of five factors was determined: the frequency setpoint of the dispensers n1, the pre-filling setpoint m, the setpoint for switching on the filling speed t, the frequency setpoint of the dispensers n2, the set weight of the suspension MZ on the dosing accuracy. At the first stage, the influence of the studied factors on grain dosing was determined. To do this, the Box-Benkin plan was implemented for five factors. As a result of the analysis of the data obtained, a regression model was built, on the basis of which three combinations of factor values were determined, in which the grain dosing error by an additional dispenser screw was 0. At the next stage of the research, the accuracy of dosing chalk and salt was determined at the established combinations. It was revealed that salt dosing was carried out according to a pattern close to the grain curve, and the dosing error was within the permissible limits of 5%. As a result of the conducted studies, the best combination of factors was determined, in which the dosing error did not exceed the permissible value when weighing grain, salt and chalk: n1 = 30.3 Hz, t = 11.9 %; n2 = 40.9 % of n1 (12.42 Hz), MZ = 202.8 g. With these values of the studied parameters, it is possible to dose components with the permissible error of the weight of the suspension is over 200 g.